Efektivitas Penggunaan Influencer dalam Strategi Pemasaran Digital - Ahmad Yusuf Kresna Andi S; Lilis Setyowati; Gentri Zulfika; Edy Sulistiyawan (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2024)
Digital marketing strategies have come a long way, but a key challenge is reaching an increasingly fragmented audience. In this context, the use of influencers in digital marketing strategies has become an effective alternative. This research explores the effectiveness of using influencers in digital marketing strategies in the rapidly evolving social media era. This research utilizes the literature review method to integrate credible references relating to digital marketing resources. The results show that planned collaboration between companies and influencers not only increases the visibility of the goods or services offered, but also builds consumer trust, which contributes to increased conversion and customer loyalty. The findings provide practical insights for marketers to design more effective digital marketing strategies, emphasizing the importance of value alignment between companies and influencers and innovation in content creation. It is desired that this research can serve as a benchmark for companies in harnessing the potential of influencers as an integral part of their digital marketing strategy.